2021
DOI: 10.1016/j.ekir.2020.10.019
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Complications Associated With Percutaneous Native Kidney Biopsies in Adults in Low- and Middle-Income Countries

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 46 publications
0
11
0
1
Order By: Relevance
“…Within the middle-income subgroups in the present review, the rate of gross hematuria was reported to be 6.4%, higher than the gross hematuria rate of 1.5% reported in a previous meta-analysis of adult native kidney biopsies in middle and low-income countries. 13 However, rates of blood transfusion (0.2% versus 0.24%), major complications (0.5% versus 1.6%), and radiological interventions (0.2% versus 0.2%) were comparable. A total of 14 studies with 1515 kidney allograft biopsies were included in the present review compared with 29 studies with almost 17 000 native kidney biopsies in the same timeframe, possibly reflecting a relative lack of experience for kidney allograft biopsies in low- to middle-income countries, which may be responsible for higher risk of gross hematuria in allograft biopsy.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Within the middle-income subgroups in the present review, the rate of gross hematuria was reported to be 6.4%, higher than the gross hematuria rate of 1.5% reported in a previous meta-analysis of adult native kidney biopsies in middle and low-income countries. 13 However, rates of blood transfusion (0.2% versus 0.24%), major complications (0.5% versus 1.6%), and radiological interventions (0.2% versus 0.2%) were comparable. A total of 14 studies with 1515 kidney allograft biopsies were included in the present review compared with 29 studies with almost 17 000 native kidney biopsies in the same timeframe, possibly reflecting a relative lack of experience for kidney allograft biopsies in low- to middle-income countries, which may be responsible for higher risk of gross hematuria in allograft biopsy.…”
Section: Discussionmentioning
confidence: 86%
“…A recent systematic review on native kidney biopsies in low-and middle-income countries also suggested that major complications were associated with lower income status. 13 The present review, to the best of our knowledge, is the first systematic review examining the outcomes of transplant kidney biopsies in both adult and pediatric populations. The review also examined several factors (age, reasons for biopsy, center biopsy volume, type of proceduralists, and income status) on the outcomes of biopsy.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Percutaneous kidney biopsy is an essential procedure for confirming a pathological diagnosis in some types of acute and chronic kidney diseases [1,2], but several complications have been linked to this procedure, including gross hematuria, hematoma, transfusion, intervention, nephrectomy, bladder obstruction, and even death [3][4][5]. Nowadays, for safety reasons, real-time ultrasound-guided percutaneous kidney biopsy is most commonly performed as evidence shows that this procedure is associated with fewer complications than the traditional biopsy method without ultrasound [6]. In some cases, however, adverse events related to kidney biopsy are still reported [5,7].…”
Section: Introductionmentioning
confidence: 99%